Theory and practice of computation : Workshop on computation: theory and practice Quezon City, Philippines, September 2011 Proceedings - Nishizaki, Shin-ya (Proceedings in Information and Communications Technology, 2012)
Computation should be a good blend of theory and practice, and researchers in the field should create algorithms to address real world problems, putting equal weight on analysis and implementation. Experimentation and simulation can be viewed as yielding to refined theories or improved applications. The Workshop on Computation: Theory and Practice (WCTP)-2011 was the first workshop organized jointly by the Tokyo Institute of Technology, the Institute of Scientific and Industrial Research-Osaka University, the University of the Philippines Diliman, and De La Salle University-Manila devoted to theoretical and practical approaches to computation. The aim of the workshop was to present the latest developments by theoreticians and practitioners in academe and industry working to address computational problems that can directly impact the way we live in society. This book comprises the refereed proceedings of WCTP-2011, held in Quezon City, the Philippines, in September 2011. The 16 carefully reviewed and revised full papers presented here deal with biologically inspired computational modeling, programming language theory, advanced studies in networking, and empathic computing.